The More Things Change…: Exploring Solutions to Persisting Discrimination in Legal Academia - Hart, Melissa (Columbia Journal of Gender and Law, 2019)
In May 2014, a conversation about gender discrimination among law school faculties exploded on the email listserv for the American Association of Law Schools (“AALS”) Section of Women in Legal Education. This conversation drew in dozens of participants from schools all over the United States and included teachers who were just starting out and those nearing retirement, drawing in clinical faculty, legal writing faculty, library faculty, and podium faculty. The topics that were raised ranged from the discriminatory actions of colleagues and students, to the marginalization of particular subject areas in the curriculum, to structural hierarchies in the profession, to the role of class in exacerbating other inequalities. The conversation went on for several weeks, and many of the participants urged that we needed to harness the feelings of anger and frustration expressed by so many and work together to channel that energy into productive change. As one step, a group of faculty members from all over the country, inspired by a suggestion from Professor Meera Deo of Thomas Jefferson School of Law, banded together to propose a “crosscutting program” at the 2015 meeting of the AALS that would draw from empirical data, legal research, litigation strategy, and personal experience to both further conversations about the persistence of discrimination in the legal academy and activate strategies for addressing continuing problems. The program had a unique structure to permit the inclusion of as many voices as possible in the conversation. The program began with a three-person panel similar to more traditional AALS presentations. The second part of the program was made up of three-minute statements by speakers who were selected in response to a “call for remarks” circulated by the program organizers. The Articles in this symposium issue represent some of the ideas that emerged from this crosscutting program. The Articles are presented here in the order that the speakers offered their remarks at the AALS program.